Aza‐Michael Addition of 5‐Substituted Tetrazole Catalysed By a Novel Nanoparticle Solid Base Catalyst Involving a Layered Zinc Hydroxide Supported on a Ferrite Core. Issue 9 (1st March 2019) - Pazoki, Farzane; Mehraban, Jamshid Azarnia; Shamsayei, Maryam; Bakhshi, Bita; Esfandiarpour, Razieh; Miraki, Maryam Kazemi; Heydari, Akbar
Abstract: Fe3 O4 @SiO2 @layered Zinc hydroxide (LZH) (0.85 mol %) efficiently was catalyzed the aza‐Michael reaction of 5‐substituted tetrazoles derivatives with α, β‐unsaturated carbonyl compound under reflux in acetonitrile to produce the new compounds. These new compounds were investigated for antibacterial activity and studied for the structural properties by theoretical calculations. Abstract : In the presence of a catalytic amount of Fe3 O4 @SiO2 @layered Zinc hydroxide (LZH) nanoparticles, efficient aza‐michael reaction of several 5‐substituted tetrazoles derivatives with α, β‐unsaturated carbonyl compound is described under reflux in acetonitrile.